Renal tumors - Antczak, Andrzej; Kalwas, Paweł; Milecki, Piotr; Stachowski, Tomasz; Cieślikowski, Wojciech; Kwias, Zbigniew (Contemporary Oncology/Współczesna Onkologia, 2002)
Renal tumors present serious problems, especially therapeutical, despite progress in medicine. The most common Renal Cell Carcinoma remains unsensible for radiotherapy and contemporary chemotherapy. Immunotherapy is still an experimental procedure, though first reports are promising. At present surgical treatment is performed as a standard and it evolves towards less invasive (laparoscopy, RF-ablation) and nephron-sparing procedures. It is important that not every renal tumor is malignant. Benign neoplasms should be diagnosed during a preoperative diagnosis to avoid unnecessary operations. The most important clinically benign tumors include: angyolipoma, oncocytoma and renal adenoma. Sometimes ultrasonography is sufficient, in other cases it is necessary to perform CT, NMR or angiography scans. Then surgical treatment is obligatory only in situations dangerous for patients like bleeding. On the other hand in malignant tumors surgery is the only way of treatment. We can choose appropriate procedure according to specific conditions, especially the condition of the other kidney. Recently nephron-sparing surgery is proposed even to patients with completely healthy second kidney. Nephron-sparing surgery includes enucleoresection and cuneal or polar resection of tumor, alternatively a brand new method: RF-ablation. Both nephron-sparing and radical resections can be also performed laparoscopically. Generally, that contemporary treatment of renal tumors includes procedures which are obligatory in specific clinical situations, minimally invasive and saving maximum of healthy tissue. At the same time, the efficacy of such treatment has to be similar to radical, traditional surgery.